Tuhan Menciptakan Manusia Laki Laki dan Perempuan: Mengenal dan Mencegah Pengaruh LGBTQ pada Remaja - Nofedin Waruwu; Lorince Tada; Tri Juliani Hia; Tasya Amelia; Shekinah Glory Mawuntu (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Global developments and advances in information technology have had a significant impact on human life, especially for the younger generation. One of the most widely discussed themes in contemporary society is LGBTQ (Lesbian, Gay, Bisexual, Transgender, and Queer). This phenomenon is now more readily found on social media, digital platforms, popular culture, and in adolescent interactions. From a Christian perspective, the issue of sexual identity is viewed based on the biblical truth that God created humans as male and female. This paper aims to explore the theological basis of human creation according to the Bible, understand the factors that influence adolescents regarding LGBTQ issues, and outline the roles of families, churches, and Christian education in assisting adolescents in facing the influence of today's sexual culture. The methodology used in this research is a literature review with a descriptive-theological approach. Data were obtained from the Bible, theological books, Christian education journals, and literature relevant to adolescent development. The analysis shows that adolescent identity formation is strongly influenced by the family environment, digital media, education, and spiritual development. Therefore, churches and families need to provide sound education, character building, and loving pastoral care so that adolescents can understand their identity in accordance with God's teachings.